The politics of migration and immigration in Europe - Geddes, Andrew, 1965-; Scholten, Peter (London : SAGE Publications Ltd, 2016)
Migration and immigration are high on any nation's agenda but have particular resonance in Europe in light of recent events. The new edition of this book has been fully updated in this respect and explores: Immigration policy in individual EU nations The treatment of migrants, including immigrant policies The development and effects of the Shengen agreement The movement towards common EU policies. It looks specifically at the contexts of Britain, France, Germany, The Netherlands, Sweden, Italy, Spain, Greece and Turkey as well as a examining the changing nature of migration dynamics in central and Eastern Europe. This book is a significant and timely analysis suitable for students of migration at any level.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Europe -- Emigration and immigration -- Government policy; Immigrants -- Government policy -- Europe